TECHNOFERENCE, COUPLE’S RELATIONSHIP SATISFACTION CORRELATION BETWEEN CONFLICT MANAGEMENT STRATEGIES CHOICE - Dudkina, Aija; Maslinovska, Lida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The aim of this scientific research article is to describe the satisfaction with pairs’ relationship and conflict management strategies choice correlation between technoference. Pairs’ relationship, their formation and long-term existence is influenced by different factors, however, important to prescribe their existence is both partners' satisfaction with them. Quality of the relationship depends on overall life satisfaction. Studies on satisfaction with the pairs relations have a tendency to grow, as evidenced by the number of research databases. For example, in 2015 the database APAPsychNet they are 32 studies, but by June 2016 already 20 studies of the relationship, which are studied more new aspects that are not so far been adequately studied. Studies have been conducted on the use of technology devices impact on pairs’ relationships satisfaction with the relationship (for example, Sidelinger, Avash,et.al., 2008, Coyne, et.al., 2011). Available sources is a study that analyzes satisfaction with the pairs’ relationships correlation with technoference (technical devices in use caused by disruption in the pairs mutual communication), which leads to the conclusion that in this perspective the topic has not yet been adequately studied (Coyne McDaniel, 2016). This study will be determined not only technoference correlation with the satisfaction of pairs relationship and conflict management strategies choice of partners, but will also explore what device causing the most disruption and whether there is technoference correlation with conflict management strategies.